Nonwoven fabric using hyaluronate fibers and method for manufacturing the same

CN118974336BActive Publication Date: 2026-11-03JINWOO BIO
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280094094.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-05-23
Filing Date
2022-05-31
Publication Date
2026-11-03
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

Existing methods for manufacturing hyaluronic acid fibers require the removal of volatile solvents, resulting in low productivity, fragile physical properties, and high costs, making it impossible to commercialize high-strength nonwoven fabrics.

Method used

By adjusting the moisture content of the hyaluronic acid paste to 50-95% by weight, melting it at 15-100°C and extruding it through a nozzle, drying it to form a rough-surfaced hyaluronic acid fiber, and then subjecting it to crimping, cutting, combing and needle punching to form a nonwoven fabric with high adhesion and tensile strength.

Benefits of technology

Mass production of high-strength hyaluronic acid nonwoven fabric has been achieved, which is suitable for topical skin patches and tissue repair biomaterials, and has excellent adhesion and tensile strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118974336B_ABST
    Figure CN118974336B_ABST
Patent Text Reader

Abstract

The present invention relates to a hyaluronic acid nonwoven fabric using hyaluronic acid fibers and a manufacturing method thereof, and more particularly, to a high-functional hyaluronic acid nonwoven fabric manufactured by a hyaluronic acid fiber having a rough surface and a minute diameter and a manufacturing method thereof. The manufacturing method of the hyaluronic acid nonwoven fabric of the present invention is characterized by comprising: (a) a step of manufacturing a hyaluronic acid fiber; (b) a step of performing a curling process on the manufactured hyaluronic acid fiber; (c) a step of cutting the hyaluronic acid fiber to which the curling is imparted; (d) a step of forming a web using the cut hyaluronic acid fiber; and (e) a step of performing needle punching on the formed hyaluronic acid web. The hyaluronic acid nonwoven fabric of the present invention contains a high concentration of hyaluronic acid, is manufactured by needle punching a high-strength hyaluronic acid fiber, has excellent adhesion and tensile strength, and can be used in various fields such as a skin external agent patch, a tissue repair biomaterial, an anti-adhesion covering material, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to hyaluronic acid nonwoven fabrics using hyaluronic acid fibers and methods for manufacturing the same, and more specifically, to a high-functionality hyaluronic acid nonwoven fabric made from hyaluronic acid fibers with a rough surface and a small diameter, and methods for manufacturing the same. Background Technology

[0002] Nonwoven fabrics are planar fibrous structures made by combining various fibers such as natural fibers, chemical fibers, glass fibers, and metal fibers into an entangled web based on their mutual characteristics and then bonding them together using mechanical or physical methods. Nonwoven fabrics are widely used in various industrial fields depending on their uses, properties, and functions. Furthermore, components that can impart secondary processing or various functionalities to nonwoven fabrics are being mixed in to conduct related research on various nonwoven fabrics.

[0003] Recently, the consumption of nonwoven fabric products has been increasing across multiple industries. For example, nonwoven fabrics are being used to produce rigid panels under high temperature and pressure for use as trim materials in automobiles or building materials. In a wide variety of fields such as clothing, hygiene, civil engineering, construction, automotive, and medical, research is focusing on developing high-value-added nonwoven fabric products with enhanced functionality, moving beyond simple product applications. Particularly in the medical market, nonwoven fabric products, in addition to surgical gowns and masks, are used not only as surgical drapes, pads, dressings, and filters, but also as tissue supports inserted for internal organ regeneration.

[0004] To manufacture this medical nonwoven fabric, a variety of biodegradable polymers are utilized. Biodegradable polymers are a general term for polymers that gradually disappear in form and weight as they undergo chemical degradation within a living organism. Representative natural polymers include collagen, fibronectin, gelatin, chitosan, and alginate. Synthetic polymers include polylactic acid (PLA), polyglycolic acid (PGA), polylactic-co-glycolic acid copolymer (PLGA) and similar copolymers, as well as polycaprolactone (PCL), polyanhydrides, and polyorthoesters.

[0005] Korean Patent No. 1329261 discloses a functional nonwoven fabric utilizing chitosan and its manufacturing method. Korean Patent No. 2002586 discloses a thermally bonded nonwoven fabric comprising natural fibers uniformly coated with chitosan on cellulose fibers.

[0006] On the other hand, hyaluronic acid (HA), a mucopolysaccharide found in the dermis, is a biopolymer composed of N-acetyl glucosamine and D-glucuronic acid linked by β-1,4 glucosidic bonds. It is a biopolymer that is linked by β-1,3 glucosidic bonds to form hyaluronic acid salt chains.

[0007] Hyaluronic acid is evenly distributed in the connective tissue, epithelium, and nerve tissue of the human body. As a biocompatible material with diverse physiological activities, its effects on skin regeneration and moisturizing, maintaining elasticity, and improving wrinkles have been proven. Therefore, recently, the industry has requested the manufacture of nonwoven fabrics using this hyaluronic acid fiber for wound dressings, cosmetic patches, and anti-adhesion coatings. However, the following problems exist with the manufacturing methods of hyaluronic acid fiber used as a raw material for nonwoven fabrics.

[0008] The manufacturing method of hyaluronic acid nanofibers requires a further removal process to remove volatile organic solvents such as DMF, DMSO, and formic acid that must be used in the manufacturing of nanofibers. When manufacturing nonwoven fabrics, nanofiber nonwoven fabrics are inconvenient to use alone and have the disadvantage of being fragile. In addition, the productivity per unit time is very low and the production unit price is high.

[0009] To address this issue, Korean Patent No. 2338355 discloses a wet-process nonwoven fabric manufacturing method. However, this method also results in fragile materials and a slightly complex manufacturing process, necessitating the research of more efficient manufacturing methods. When used in the form of nonwoven fabric, the inability to achieve properties exceeding a predetermined strength hinders the necessary processing operations such as material preparation for product manufacturing, making commercialization difficult.

[0010] Therefore, the inventors devoted themselves to solving the aforementioned problems and discovered that by manufacturing a hyaluronic acid paste with a moisture content of 50-95% by weight, melting it, extruding it through a nozzle, and drying it, hyaluronic acid fibers with a rough surface and excellent tensile strength can be mass-produced. Furthermore, by using it for needle punching, hyaluronic acid nonwoven fabrics with excellent adhesion and tensile strength can be manufactured, thus completing the present invention. Summary of the Invention

[0011] Technical issues The purpose of this invention is to provide a hyaluronic acid salt nonwoven fabric and its manufacturing method, which not only adheres well to the skin or body but also has excellent mechanical properties required for processing, making it effective as a skin patch, tissue repair biomaterial, or anti-adhesion covering material.

[0012] Technical solution To achieve the above objectives, the present invention provides a hyaluronic acid nonwoven fabric containing hyaluronic acid fibers, characterized in that, when measured by the following measurement method, the bending angle is 2 to 10°, the moisture content is 5 to 25% by weight, and the hyaluronic acid content is 90% by weight or more relative to the total weight of the fibers excluding moisture.

[0013] <Method for Measuring Bending Angle> (a) Prepare HA fibers with a length of 20 cm and a diameter of 1 mm. (b) Fix one end of the HA fiber 3 cm to the top of the plate. (c) Using the upper extension line (B) of the plate as a reference, measure the angle (θ) formed by the extension line (T) of the other end of the HA fiber.

[0014] In this invention, the tensile strength of the hyaluronic acid fiber is characterized by being 3-15 kg / m³. .

[0015] In this invention, the adhesive strength of the hyaluronic acid nonwoven fabric is 0.9~2.7 kPa.

[0016] In this invention, the thickness of the hyaluronic acid nonwoven fabric is 1~10 mm.

[0017] In this invention, the tensile strength of the hyaluronic acid nonwoven fabric is characterized by being 0.3~1.5 kg / m³. .

[0018] In this invention, the hyaluronic acid nonwoven fabric is used as a skin patch, tissue repair biomaterial, or anti-adhesion covering material.

[0019] The present invention provides a method for manufacturing a hyaluronic acid nonwoven fabric, characterized by comprising: (a) a step of manufacturing hyaluronic acid fibers; (b) a step of crimping the manufactured hyaluronic acid fibers; (c) a step of cutting the hyaluronic acid fibers that have been crimped; (d) a step of forming a web using the cut hyaluronic acid fibers; and (e) a step of needle punching the formed hyaluronic acid web.

[0020] In this invention, the step of manufacturing hyaluronic acid fibers comprises: (a-1) adjusting the moisture content of hyaluronic acid with a weight-average molecular weight of 100 to 3,000 kDa to 50 to 95% by weight to manufacture a hyaluronic acid paste; (a-2) melting the hyaluronic acid paste with adjusted moisture content at 15 to 100°C and then extruding it through a nozzle; and (a-3) drying the extruded spinning fluid to form fibers.

[0021] In this invention, the characteristic is that, when forming the web, fibers made from a polymeric material selected from the group consisting of collagen, fibronectin, gelatin, chitosan, alginate, polylactic acid (PLA), polyglycolic acid (PGA), polylactic-co-glycolic acid copolymer (PLGA), and polycaprolactone (PCL) are mixed.

[0022] Invention Effects The hyaluronic acid salt nonwoven fabric of the present invention contains a high concentration of hyaluronic acid salt and is manufactured by needle punching high-strength hyaluronic acid salt fibers, and has excellent adhesion and tensile strength. Attached Figure Description

[0023] Figure 1 These are photographs evaluating the roughness of hyaluronic acid fibers according to an embodiment of the present invention. (A: Smooth hyaluronic acid fibers, B: Rough hyaluronic acid fibers) Figure 2 This is an explanatory diagram of a method for measuring the bending angle of hyaluronic acid fibers according to an embodiment of the present invention.

[0024] Figure 3 This is a photograph of hyaluronic acid fiber according to an embodiment of the present invention. (A: Hyaluronic acid fiber, B: Hyaluronic acid fiber with curl) Figure 4 This is a photograph of a hyaluronic acid nonwoven fabric manufactured by needle punching according to an embodiment of the present invention.

[0025] Figure 5 This is a photograph of a nonwoven fabric made of hyaluronic acid salt and chitosan according to an embodiment of the present invention.

[0026] Figure 6 These are microstructure photographs of the needle-punched nonwoven fabric of the present invention. (A: Hyaluronic acid salt nonwoven fabric, B: Hyaluronic acid salt and chitosan mixed nonwoven fabric) Detailed Implementation The best way to implement an invention In this invention, it is confirmed that when a hyaluronic acid paste with a moisture content adjusted to a specific range is spun through a nozzle at a predetermined temperature and simultaneously dried at a high temperature and a very low temperature, a hyaluronic acid fiber with a very rough fiber surface can be produced. When needle-punched, a nonwoven fabric with excellent adhesion and mechanical strength can be produced.

[0027] In this invention, the water content of hyaluronic acid salts is adjusted to 50-95% by weight to manufacture a paste. The hyaluronic acid salt paste is melted at 15-100°C and extruded through a nozzle, then dried at 100-150°C. This process produces a large quantity of hyaluronic acid salts with a water content of 5-25% by weight and a tensile strength of 3-15 kg / m³. A very rough surface of hyaluronic acid fiber. After heating the manufactured hyaluronic acid fiber to induce curl, it is cut to a predetermined length, formed into a web by carding and airflow web formation, and then needle-punched. The resulting nonwoven fabric is then pressed to produce a nonwoven fabric with excellent adhesion and tensile strength.

[0028] Therefore, the present invention relates to a method for manufacturing a hyaluronic acid nonwoven fabric, characterized by comprising: (a) a step of manufacturing hyaluronic acid fibers; (b) a step of crimping the manufactured hyaluronic acid fibers; (c) a step of cutting the hyaluronic acid fibers that have been crimped; (d) a step of forming a web using the cut hyaluronic acid fibers; and (e) a step of needle punching the formed hyaluronic acid web.

[0029] In this invention, the steps of manufacturing hyaluronic acid fibers include: (a-1) adjusting the moisture content of hyaluronic acid with a weight-average molecular weight of 100 to 3,000 kDa to 50 to 95% by weight to manufacture a hyaluronic acid paste; (a-2) melting the hyaluronic acid paste with adjusted moisture content at 15 to 100°C and then extruding it through a nozzle; and (a-3) drying the extruded spinning fluid to form fibers.

[0030] In this invention, hyaluronic acid salts are substances in which salts are bound to hyaluronic acid, such as sodium hyaluronate, calcium hyaluronate, potassium hyaluronate, etc., but are not limited to these.

[0031] In this invention, the molecular weight of the hyaluronic acid salt is preferably 100-3,000 kDa. Furthermore, the hyaluronic acid salt paste is characterized by a water content of 50-95% by weight.

[0032] The hyaluronic acid paste can be manufactured by adding a solvent to the hyaluronic acid, preferably a water or ethanol solution, and mixed until the solvent is homogeneously mixed.

[0033] In order to successfully carry out the mass spinning process, the moisture content of the hyaluronic acid paste can be 50-95% by weight, preferably 88-92% by weight. When the moisture content is less than 50% by weight, high pressure is required during spinning. When the moisture content exceeds 95% by weight, it is in liquid form compared to the paste, and therefore there is a problem of filament breakage during spinning.

[0034] In this invention, the key feature is that after manufacturing the hyaluronic acid paste, a step of placing it at 0-100°C for 6-12 hours is performed to achieve moisture balance. Moisture balance cannot be achieved properly when the temperature and time ranges are exceeded. This moisture balance is used to ensure that the water molecules in the paste are uniformly mixed with the hyaluronic acid. When spinning is performed without moisture balance, the water molecules and hyaluronic acid are not mixed uniformly, thus preventing spinning from proceeding at the predetermined speed.

[0035] In this invention, a hyaluronic acid salt paste with a moisture content adjusted to 50-95% by weight can be added to a spinning device, melted at 15-100°C, and then extruded through a nozzle to produce a spinning fluid. At this point, if the temperature is below 15°C, the hyaluronic acid salt paste will not melt and cannot be extruded; if the temperature exceeds 100°C, the paste will boil.

[0036] In this invention, fibers are ultimately formed by drying the extruded spinning fluid. This drying is preferably carried out at 100-150°C, depending on the moisture content of the paste. When the drying temperature is below 100°C, the surface of the manufactured fibers is smooth, resulting in weak entanglement during needle punching after web formation, making it difficult to form nonwoven fabrics. Above 150°C, problems such as fiber browning and cracking occur.

[0037] The manufactured hyaluronic acid fibers can have a hyaluronic acid content of over 90% by weight, a moisture content of 5-25% by weight, and a tensile strength of 3-15 kg / m³. Its surface is very rough, so when it is used to manufacture nonwoven fabrics, nonwoven fabrics with a variety of densities and physical properties can be produced.

[0038] The method for manufacturing the hyaluronic acid nonwoven fabric of the present invention is characterized by imparting curl by means of heat treatment or the like to increase the inter-fiber cross-linking force. During heat treatment, curl can be imparted by hot air treatment of the hyaluronic acid fibers at a high temperature of 70°C or above.

[0039] To form a web for manufacturing nonwoven fabric, the prepared hyaluronic acid fibers can be cut to the desired length and then formed into a web using a carding and air-blowing process. That is, the cut hyaluronic acid fibers are dispersed by air pressure and then ejected by air pressure to form a web.

[0040] The needle-punching step of this invention involves needle-punching the formed planar sheet-like web. Specifically, the needle-punching step involves repeatedly moving a needle plate with needles up and down while passing through a needle-punching machine, so that a portion of the two-dimensional random fiber arrangement combines into a three-dimensional random structure to manufacture nonwoven fabric.

[0041] In the method for manufacturing hyaluronic acid nonwoven fabric of the present invention, fibers made of biocompatible materials can be mixed during web formation. That is, in order to ensure a wider variety of physical and functional properties, pharmacologically acceptable biocompatible materials that can be used to manufacture fibers, such as collagen, fibronectin, gelatin, chitosan, alginate, polylactic acid (PLA), polyglycolic acid (PGA), polylactic-co-glycolic acid copolymer (PLGA), and polycaprolactone (PCL), can be mixed with hyaluronic acid fibers.

[0042] Another aspect of the present invention relates to a hyaluronic acid nonwoven fabric comprising hyaluronic acid fibers, characterized in that, when measured by the following measurement method, the bending angle is 2 to 10°, the moisture content is 5 to 25% by weight, and the hyaluronic acid content is 90% by weight or more relative to the total weight of the fibers excluding moisture.

[0043] <Method for Measuring Bending Angle> (a) Prepare HA fibers with a length of 20 cm and a diameter of 1 mm. (b) Fix one end of the HA fiber 3 cm to the top of the plate. (c) Using the upper extension line (B) of the plate as a reference, measure the angle (θ) formed by the extension line (T) of the other end of the HA fiber. The tensile strength of the hyaluronic acid fiber is 3~15 kg / m³. Therefore, nonwoven fabrics can be manufactured using needle punching. The tensile strength of hyaluronic acid fibers is less than 3 kg / m³. At this point, the fiber is highly likely to break, making it difficult to process, especially when the weight exceeds 15kg / kg. At that time, the material was rigid, and when it was made into non-woven fabric, it may cause inconvenience in use.

[0044] The hyaluronic acid hyaluronic acid nonwoven fabric of the present invention preferably has a thickness of 1 to 10 mm, and the resulting nonwoven fabric is characterized by having a density of 0.3 to 1.5 kg / m³ depending on the thickness of the nonwoven fabric. The tensile strength and adhesion are 0.9~2.7 kPa.

[0045] The hyaluronic acid nonwoven fabric of the present invention has excellent adhesion and tensile strength, and can be used as a skin patch, tissue repair biomaterial, anti-adhesion covering material, etc.

[0046] Specific methods of implementing the invention The present invention will be described in more detail below through embodiments. These embodiments are for illustrative purposes only and should not be construed as limiting the scope of the invention to these embodiments, which is self-evident to those skilled in the art.

[0047] Example 1: Preparation of hyaluronic acid salt paste Sodium hyaluronate with a molecular weight of 150 kDa (Hi-Aqua) TM A hyaluronic acid paste with a moisture content of 50-95% by weight was prepared by adding water and mixing the paste with water. The prepared hyaluronic acid paste was then refrigerated at 4°C for 12 hours to promote moisture balance.

[0048] Example 2: Manufacturing hyaluronic acid cellulose fibers by spinning The hyaluronic acid paste prepared in Example 1 was placed in the storage section of the spinning device, melted at 15~100°C, pressurized and spun through a nozzle, and dried at 120°C to produce hyaluronic acid fibers with a moisture content of 5~25% by weight.

[0049] Comparative Example 1: Manufacturing hyaluronic acid cellulose fibers by spinning The hyaluronic acid paste prepared in Example 1 was placed in the storage section of the spinning device, melted at 15~100°C, pressurized and spun through a nozzle, and dried at 50°C to produce hyaluronic acid fibers with a moisture content of 5~25% by weight.

[0050] Comparative Example 2: Manufacturing hyaluronic acid cellulose fibers by spinning The hyaluronic acid paste prepared in Example 1 was placed in the storage section of the spinning device, melted at 15~100°C, pressurized and spun through a nozzle, and dried at 160°C to produce hyaluronic acid fibers.

[0051] Experimental Example 1: Evaluation of fiber roughness of hyaluronic acid fibers at different drying temperatures The surface roughness of the fibers obtained in Example 2, Comparative Example 1, and Comparative Example 2 was evaluated using a microscope. Figure 1 ).

[0052] As a result, fibers with a moisture content of 5-25% by weight were spun under drying conditions of 50°C (Comparative Example 1) and 120°C (Example 2). It was confirmed that the surface of the fibers dried at 50°C was smooth, while the surface of the fibers dried at 120°C was rough. Comparative Example 2, with a moisture content of 1-5% by weight and a drying temperature of 160°C, showed excessive browning and crack formation in the fibers.

[0053] Experiment Example 2: Measuring the bending angle of hyaluronic acid fibers The bending angle of the hyaluronic acid fibers prepared in Example 2 was measured using the following method (refer to...). Figure 2 The results are shown in Table 1.

[0054] (a) Prepare HA fibers with a length of 20 cm and a diameter of 1 mm. (b) Fix one end of the HA fiber 3 cm to the top of the plate. (c) Using the upper extension line (B) of the plate as a reference, measure the angle (θ) formed by the extension line (T) of the other end of the HA fiber. Table 1

[0055] As can be seen from Table 1 above, when the moisture content of hyaluronic acid fibers exceeds 25% by weight, the bending angle exceeds 10°, making it difficult to form a web or to manufacture nonwoven fabrics by needle punching. Even if nonwoven fabrics are manufactured, the reduced physical properties will prevent the processing operations such as material cutting required for productization, thus posing a problem for commercialization.

[0056] In addition, it can be confirmed that when the water content of hyaluronic acid fibers is less than 5% by weight, although the fiber shape is maintained, it is stiff and lacks flexibility, and therefore is easy to break.

[0057] Conversely, it can be seen that when the water content of hyaluronic acid fiber is 5-25% by weight, the bending angle is 2-10°, making hyaluronic acid fiber a suitable form for needle-punching nonwoven fabric manufacturing.

[0058] Experimental Example 3: Measuring the tensile strength of hyaluronic acid fibers The tensile strength of the hyaluronic acid fibers prepared in Example 2 was measured and the results are shown in Table 2. A 5 cm long sample was fitted into the test fixture, and the tensile strength was measured using a universal testing machine at a crosshead speed of 2 mm / min.

[0059] Table 2

[0060] As can be seen from Table 2 above, when the water content of hyaluronic acid fiber is above 50% by weight, the tensile strength drops sharply, it is easy to break, and it has no elasticity, so it cannot perform the function of the fiber normally.

[0061] In addition, when the water content of hyaluronic acid fibers is below 5% by weight, although the fiber shape is maintained, it is stiff and easily broken, so the tensile strength cannot be measured.

[0062] Conversely, it can be seen that when the water content of hyaluronic acid fibers is 5-25% by weight, the tensile strength is 3.24-13.38 kg / m³. Thus, hyaluronic acid fibers can function as filaments.

[0063] Example 3: Manufacturing hyaluronic acid salt nonwoven fabric by needle punching 1) Manufacturing hyaluronic acid fibers Using the method described in Example 2, hyaluronic acid fibers with a bending angle of 2-10°, a moisture content of 5-25% by weight, and a hyaluronic acid content of 90% by weight or more relative to the total weight of the fibers excluding moisture were manufactured (tensile strength: 3-15 kg / m³). () Figure 3 (A in the middle).

[0064] 2) Curling treatment The prepared hyaluronic acid fibers were hot-air treated at 70-100°C to produce hyaluronic acid fibers with a curled texture. Figure 3 (B in the middle).

[0065] 3) Cutting The curled hyaluronic acid fibers are cut into predetermined lengths of 3-7 cm using a cutting machine.

[0066] 4) A network is formed through combing and airflow. After the cut hyaluronic acid fibers are dispersed by air pressure, they are then ejected by air pressure to form a web.

[0067] 5) Acupuncture A multi-layered sheet, formed into a web, was needle-punched to produce a uniform nonwoven fabric (average thickness 5 mm). Figure 4 ).

[0068] Comparative Example 3: Manufacturing of hyaluronic acid salt nonwoven fabric by needle punching Using the method of Comparative Example 1, hyaluronic acid fibers with a bending angle of 2-10°, a moisture content of 5-25% by weight, and a hyaluronic acid content of 90% by weight or more relative to the total weight of the fibers excluding moisture were manufactured (tensile strength: 3-15 kg / m³). Using this, a hyaluronic acid salt nonwoven fabric was manufactured in the same manner as in Example 3.

[0069] The results confirmed that when using smooth hyaluronic acid fibers, the fiber entanglement force was weak during the needle punching process after the web was formed, making it impossible to form a good nonwoven fabric.

[0070] Example 4: Manufacturing a nonwoven fabric composed of hyaluronic acid salt and chitosan by needle punching 1) Manufacturing hyaluronic acid fibers Using the method of Example 2, hyaluronic acid fibers with a bending angle of 2-10°, a moisture content of 5-25% by weight, and a hyaluronic acid content of 90% by weight or more relative to the total weight of the fibers excluding moisture were manufactured (tensile strength: 3-15 kg / m³). ).

[0071] 2) Chitosan fiber Manufacturer: Saturn Biotechnology, Diameter 0.006~0.018mm 3) Curling treatment The prepared hyaluronic acid fibers were hot-air treated at a high temperature of 70~100℃ to produce hyaluronic acid fibers with curl.

[0072] Chitosan fibers with curl were produced by heat treatment with steam at 100°C or above, or by the same heat treatment process as hyaluronic acid salts.

[0073] 4) Cutting The curled hyaluronic acid and chitosan fibers are cut to a predetermined length of 3-7 cm using a cutting machine.

[0074] 5) A network is formed through combing and airflow, followed by needle punching. Cut hyaluronic acid salt fibers and chitosan fibers were mixed at a weight ratio of 50:50 and processed in the same manner as in Example 3, ultimately producing a nonwoven fabric (average thickness 5 mm) composed of hyaluronic acid salt and chitosan. Figure 5 ).

[0075] Experiment Example 4: Confirmation of the microstructure of nonwoven fabrics The fine structure of the hyaluronic acid nonwoven fabrics manufactured in Examples 3 and 4 was confirmed using a microscope (CX33RTFS2, Olympus Corporation, South Korea). Figure 6 The web-like structure of nonwoven fabrics with inter-fiber cross-linking can be confirmed, especially nonwoven fabrics mixed with chitosan, confirming the good blending of hyaluronic acid cellulose fibers and chitosan fibers. Compared with nonwoven fabrics manufactured by wet spinning, web-like nonwoven fabrics have space between the inter-fiber cross-linking, resulting in superior physical properties and ease of processing and use.

[0076] Experimental Example 5: Measurement of the gelation degree of hyaluronic acid nonwoven fabric The degree of gelation of a pure hyaluronic acid salt nonwoven fabric manufactured by needle punching (Example 3) and a nonwoven fabric containing 50% by weight each of hyaluronic acid salt and chitosan (Example 4) were measured as shown below.

[0077] Two 2×2cm sheets of pure hyaluronic acid salt nonwoven fabric and two nonwoven fabrics containing 50% hyaluronic acid salt and 50% chitosan were immersed in purified water for 5 seconds, then removed, and their external moisture was removed. The weight and degree of gelation were measured. The degree of gelation was calculated as follows.

[0078] Degree of gelation (%) = (Weight after gelation - Weight before gelation / Weight before gelation) × 100 Table 3

[0079] It is known that nonwoven fabrics containing chitosan have very low water solubility and lower gelation degree than pure hyaluronic acid salt nonwoven fabrics.

[0080] Experiment Example 6: Testing the adhesion of hyaluronic acid salt nonwoven fabric Using a texture analyzer (TA) (QM100SN, Qmesys, Korea), the adhesion of a pure hyaluronic acid salt nonwoven fabric manufactured by needle punching (Example 3, pure hyaluronic acid salt nonwoven fabric with a moisture content of 25% by weight) and a nonwoven fabric containing 50% hyaluronic acid salt and 50% chitosan respectively (Example 4, hyaluronic acid salt + chitosan nonwoven fabric with a moisture content of 25% by weight, 50:50 by weight ratio) was measured as follows.

[0081] After cutting the pigskin into 3×3cm rectangles, it was placed in room temperature water for 24 hours to adjust the moisture content to 22.3%. The pigskin was then attached to the upper and lower probes of a texture analyzer. Then, 2×2cm rectangles of pure transparent hyaluronic acid salt nonwoven fabric, nonwoven fabric mixed with chitosan, and nonwoven fabric composed only of chitosan were placed on the pigskin below. The fabric was pressed with a pressure of 3.2 kPa for 3 minutes, and then peeled off at a speed of 10 mm / min and the adhesion was measured.

[0082] Table 4

[0083] It can be confirmed that nonwoven fabrics composed solely of pure chitosan have no adhesive strength. It is known that nonwoven fabrics composed solely of hyaluronic acid salts have higher adhesive strength than those mixed with chitosan; this is because higher gelation levels increase adhesive strength.

[0084] Furthermore, it is known that nonwoven fabrics mixed with chitosan also exhibit a certain adhesive force.

[0085] Therefore, it can be seen that by mixing appropriate amounts of hyaluronic acid salts and chitosan, and manufacturing nonwoven fabrics, adjusting the degree of gelation, and endowing them with targeting ability through continuous in vivo regulation and the imparting of adhesiveness, high-performance nonwoven fabrics can be manufactured.

[0086] Experiment Example 7: Measuring the tensile strength of hyaluronic acid nonwoven fabric The tensile strengths of a pure hyaluronic acid salt nonwoven fabric manufactured by needle punching (Example 3, pure hyaluronic acid salt nonwoven fabric with a moisture content of 25% by weight) and a nonwoven fabric containing 50% hyaluronic acid salt and 50% chitosan (Example 4, hyaluronic acid salt + chitosan nonwoven fabric with a moisture content of 25% by weight, 50:50 by weight ratio) were measured, and the results are shown in Table 5. A 5 cm long sample was mounted in the test fixture, and the tensile strength was measured using a universal testing machine at a crosshead speed of 2 mm / min.

[0087] Table 5

[0088] Table 5 shows that chitosan fibers are mixed into pure hyaluronic acid cellulose fibers, resulting in higher tensile strength. This indicates that when chitosan fibers are mixed in during the formation of nonwoven fabrics, the chitosan fibers entangle within the hyaluronic acid cellulose nonwoven fabric, exhibiting stronger bonding.

[0089] The foregoing has described in detail specific parts of the present invention. This specific description is merely a preferred embodiment and is not intended to limit the scope of the invention, as is self-evident to those skilled in the art. Therefore, the essential scope of the present invention is defined by the appended claims and their equivalents.

[0090] Industrial applicability The hyaluronic acid nonwoven fabric of the present invention has excellent adhesion and tensile strength, and therefore can be used in a variety of fields such as skin topical patches, tissue repair biomaterials, and anti-adhesion covering materials.

Claims

1. A hyaluronic acid needle-punched nonwoven fabric comprising hyaluronic acid fibers, characterized in that, When measured using the following methods, the bending angle is 2–10°, the moisture content is 5–25% by weight, and the hyaluronic acid content, with a weight-average molecular weight of 150 kDa–3,000 kDa, is 90% by weight or more relative to the total weight of the fibers excluding moisture. <Method for Measuring Bending Angle> (a) Prepare HA fibers with a length of 20 cm and a diameter of 1 mm. (b) Fix one end of the HA fiber 3 cm to the top of the plate. (c) Using the upper extension line B of the plate as a reference, measure the angle (θ) formed by the extension line T of the other end of the HA fiber. The surface of the hyaluronic acid fiber is rough when observed under a microscope, and the thickness of the hyaluronic acid needle-punched nonwoven fabric is 5~10 mm.

2. The hyaluronic acid phosphate needle-punched nonwoven fabric according to claim 1, characterized in that, The tensile strength of the hyaluronic acid fiber is 3~15 kg / m³. .

3. The hyaluronic acid phosphate needle-punched nonwoven fabric according to claim 1, characterized in that, The adhesive strength of the hyaluronic acid salt needle-punched nonwoven fabric is 0.9~2.7 kPa.

4. The hyaluronic acid phosphate needle-punched nonwoven fabric according to claim 1, characterized in that, The tensile strength of the hyaluronic acid needle-punched nonwoven fabric is 0.3~1.5 kg / m³. .

5. The hyaluronic acid salt needle-punched nonwoven fabric according to claim 1, characterized in that, The hyaluronic acid needle-punched nonwoven fabric is used as a skin patch, tissue repair biomaterial, or anti-adhesion covering material.

6. A method for manufacturing the hyaluronic acid hyaluronic acid needle-punched nonwoven fabric of claim 1, characterized in that, include: (a) The steps of manufacturing hyaluronic acid fibers with a rough surface for microscopic observation; (b) The step of crimping the manufactured hyaluronic acid fibers; (c) The step of cutting the hyaluronic acid fibers that have been curled; (d) The step of forming a web using cut hyaluronic acid fibers; and (e) The step of needle punching the formed hyaluronic acid fiber network, The steps for manufacturing hyaluronic acid fibers with a rough surface for microscopic observation include: (a-1) Adjusting the moisture content of hyaluronic acid salts with a weight average molecular weight of 150 to 3,000 kDa to 50 to 95% by weight to prepare a hyaluronic acid salt paste, and placing the hyaluronic acid salt paste at 0 to 100°C for 6 to 12 hours to achieve moisture balance. (a-2) The step of melting the hyaluronic acid salt paste, which has achieved moisture balance, at 15–100°C and then extruding it through a nozzle; and (a-3) The step of drying the extruded spinning fluid at 100~150°C to form fibers.

7. The method for manufacturing hyaluronic acid sorbate needle-punched nonwoven fabric according to claim 6, characterized in that, The tensile strength of the manufactured hyaluronic acid fiber is 3~15 kg / m². .

8. The method for manufacturing hyaluronic acid phosphate needle-punched nonwoven fabric according to claim 6, characterized in that, In forming the web, fibers made from a polymeric material selected from the group consisting of collagen, fibronectin, gelatin, chitosan, alginate, polylactic acid (PLA), polyglycolic acid (PGA), polylactic-co-glycolic acid copolymer (PLGA), and polycaprolactone (PCL) are mixed.

Citation Information

Patent Citations

  • Functional non-woven fabric using chitosan and manufacturing method thereof​

    KR101329261B1

  • Thermal Bonded Nonwoven With Natural Fibers

    KR102002586B1

  • Method Of Producing Hyaluronic Acid Non Woven Fabric

    KR102338355B1